Assessment of the energy consumption and technologies in the bakery and pastry sector - Morais, Diogo (2019)
Submitted by GASPAR (dinis@ubi.pt) on 2019-10-25T15:48:23Z No. of bitstreams: 1 EGYPRO_SI_ICSEF_2018_r4.pdf: 404609 bytes, checksum: 2fe112c45ff1179eb1bd5a27ade06985 (MD5)